Strategi Pengembangan Potensi Wisata Budaya di Distrik Seram Bakon, Kabupaten Pegunungan Bintang - Atek, Liboria Genoveva (Pusat Studi Pariwisata Universitas Gadjah Mada, 2026)
The potential of cultural tourism is the gateway to tourism development. This study aims to analyze the potential for cultural tourism in Seram Bakon District. This study uses a descriptive research method using a qualitative approach. The data sources used are primary and secondary data. The purpose of the research is to identify the potential of cultural tourism and analyze its development strategy. Data collection techniques by means of observation, interviews and documentation. The data analysis method uses SWOT analysis. The results of the study show that internal factors that support the development of cultural tourism include the beauty, authenticity, uniqueness of cultural tourism objects such as museums, dances and cemeteries are still maintained today, among the factors that inhibit the development of cultural tourism are inadequate facilities and infrastructure, lack of human resources, lack of understanding of the younger generation and the community related to tourism. External factors that are challenges in the development of cultural tourism potential are the security situation (areas prone to armed conflict), the Dutch missionaries have brought cultural objects, the development of the times (modernization, assimilation and westernization) and the lack of promotion of Tourism. The cultural tourism development strategy based on SWOT is to add and develop more complete infrastructure and tourism support facilities, increase human resources, increase skill capacity and empower tourism in the younger generation, cultural experts and local communities, increasing security and comfort in tourist destination areas, as well as promoting tourism more effectively through mass media; television, radio, newspapers, and social media; Facebook, Instagram, TikTok, Twitter, and the website of the Tourism and Creative Economy Office of Pegunungan Bintang Regency